1999
DOI: 10.1159/000018090
|View full text |Cite
|
Sign up to set email alerts
|

Short-Time Extracorporeal Photochemotherapy in the Treatment of Drug-Resistant Autoimmune Bullous Diseases

Abstract: Background: Bullous pemphigoid (BP) and pemphigus vulgaris (PV) are potentially severe diseases. In drug-resistant PV and pemphigus foliaceus, long-term adjuvant treatment with extracorporeal photochemotherapy (photopheresis, ECP) has been reported to induce remission. Only limited numbers of patients have been reported so far. No information about the effectiveness in drug-resistant BP is available. Patients and Methods: Seven patients with drug-resistant autoimmune bullous diseases have been referred to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 19 publications
0
36
0
3
Order By: Relevance
“…We included ECP in our protocol in order to obtain long-term immunotolerance. Wollina et al [4] showed how all the drugresistant BP patients in their study achieved a complete response after a limited number of ECP cycles alone. Similarly to these authors, we observed a complete clinical response after a limited number of ECP procedures in both acute and chronic GvHD in children (unpublished personal data); we, therefore, opted to include only four ECP procedures in our protocol.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We included ECP in our protocol in order to obtain long-term immunotolerance. Wollina et al [4] showed how all the drugresistant BP patients in their study achieved a complete response after a limited number of ECP cycles alone. Similarly to these authors, we observed a complete clinical response after a limited number of ECP procedures in both acute and chronic GvHD in children (unpublished personal data); we, therefore, opted to include only four ECP procedures in our protocol.…”
Section: Discussionmentioning
confidence: 94%
“…Two studies [13,14] showed the benefit of plasmapheresis as steroid saving agent; although the literature regarding the use of plasmapheresis in drug-resistant BP is scant [2,3,[15][16][17], it does show that a general improvement in clinical symptoms and remission allows a subsequent reduction in the required dose of corticosteroids. The use of ECP in BP is poorly investigated: only one study [4] has reported a response in drug-resistant BP using a short-time ECP protocol. Inflammatory bowel diseases (IBD) are considered to be systemic autoimmune diseases since they are often associated with extraintestinal manifestations, complications, and other autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tüm vakalarda klinik iyileşme görülmüş ve eşzamanlı kullanılan prednizolon ve diğer immünsüpresif ilaçların dozları düşürülebilmiştir (14).…”
Section: Ekstra Korporal Fotokemoterapi (Ekf)unclassified
“…Other Dermatological Diseases ECP treatment has been proposed in several autoimmune dermatological diseases, including pemphigus bullosus and vulgaris, in drug-resistant patients or as an adjuvant therapy [48][49][50], with satisfactory results in 60-75% of patients. Similar findings regarding ECP treatment have been published in epidermolysis bullosa [51], chronic erosive lichen planus [52] and atopic dermatitis [53].…”
Section: Ctclmentioning
confidence: 99%